PERAN KEPOLISIAN DALAM MENANGGULANGI TINDAK PIDANA PERJUDIAN GELPER DI WILAYAH KOTA BATAM: PERAN KEPOLISIAN DALAM MENANGGULANGI TINDAK PIDANA PERJUDIAN GELPER DI WILAYAH KOTA BATAM - Aulia, Novia (SCIENTIA JOURNAL, 2024)
Seeing the development of the current era, as well as the rapid advancement of technology, certainly has aninfluence both from the positive and negative sides. Riau Islands, especially Batam City itself is a city that is directlyadjacent to neighboring countries. This certainly has a lot of influence on the city itself, where the City adopts manycultural cultures from neighboring countries, starting from the culture that builds Batam City in a better direction,but also adopts its entertainment culture such as gambling, where gambling itself is prohibited in Indonesia. Inwriting this thesis, the author has a goal, namely first, to find out the process of gambling law enforcement,especially this GELPER gambling in Batam City Then its relevance to the Gambling Law; second, to find out theprecautions taken by the Riau Islands POLDA in the process of tackling GELPER gambling in Batam City; Third,to find out the obstacles and obstacles of the Riau Islands POLDA in handling the GELPER gambling case inBatam City. This type of panelitian is an empirical panelitian where the author directly conducts an interview at theRiau Islands POLDA office, and pours it in a descriptive form which means describing through writing what theauthor has obtained in the field. Then from the results of the interview, the author found the results of research inwhich the gambling case carried out in the game arena still cannot be ascertained. and concluded that gamblingcases in the gaming arena already exist, but no case has yet entered the Batam City Police Chief.